2021
DOI: 10.1186/s12864-021-07985-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics and transcriptome analysis at different anther development stages of the male sterile mutant MS7–2 in Wucai (Brassica campestris L.)

Abstract: Background The discovery of male sterile materials is of great significance for the development of plant fertility research. Wucai (Brassica campestris L. ssp. chinensis var. rosularis Tsen) is a variety of non-heading Chinese cabbage. There are few studies on the male sterility of wucai, and the mechanism of male sterility is not clear. In this study, the male sterile mutant MS7–2 and the wild-type fertile plant MF7–2 were studied. Results Phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Similar findings were observed in the Brassica anthers of MF7-2, which developed normally and possessed many plump pollen grains. The filaments of MS7-2 were short, and the anthers were abnormally degraded, with no obvious pollen grains on the surface [33]. The BTx623 s (wild-type sorghum) mature spikelet (sessile spikelet) contains three extruding yellow anthers and two stigmas with pollen grains.…”
Section: Morphological Observations Of Male-sterile and Fertile Anthersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were observed in the Brassica anthers of MF7-2, which developed normally and possessed many plump pollen grains. The filaments of MS7-2 were short, and the anthers were abnormally degraded, with no obvious pollen grains on the surface [33]. The BTx623 s (wild-type sorghum) mature spikelet (sessile spikelet) contains three extruding yellow anthers and two stigmas with pollen grains.…”
Section: Morphological Observations Of Male-sterile and Fertile Anthersmentioning
confidence: 99%
“…Mutation in this locus leads to the replacement of amylose with amylopectin [38]. The starch deposition is controlled gametophytically, and hence fertility restoration in CMS plants is gametophytic in nature [18,19,33]. The findings in sorghum suggested that the deterioration of pollen grains was associated with an increase in reactive oxygen species (ROS) with a significant reduction in phospholipid levels.…”
Section: Cytomorphological Observations Of Fertile Partially Fertile ...mentioning
confidence: 99%
“…Flow cytometry (FCM) and chromosome counting, as well as observation of morphological and physiological characteristics, are widely applied for determining ploidy levels in plants (Ferreira et al, 2021;Wang et al, 2021). Among them, chromosome counting is the most direct and accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, breeding of pollen-free lily varieties is an urgent need for promoting cut-flower lily production. In previous studies, new pollen-free varieties were developed mainly through traditional crossbreeding and mutagenesis breeding (Wang et al, 2021). Pollen-free F1 was produced through hybridisation, and a set of pollenfree genetic traits was established.…”
mentioning
confidence: 99%